2016
DOI: 10.1007/s13361-016-1508-8
|View full text |Cite
|
Sign up to set email alerts
|

TEMPO-Assisted Free Radical-Initiated Peptide Sequencing Mass Spectrometry (FRIPS MS) in Q-TOF and Orbitrap Mass Spectrometers: Single-Step Peptide Backbone Dissociations in Positive Ion Mode

Abstract: The present study demonstrates that one-step peptide backbone fragmentations can be achieved using the TEMPO [2-(2,2,6,6-tetramethyl piperidine-1-oxyl)]-assisted free radical-initiated peptide sequencing (FRIPS) mass spectrometry in a hybrid quadrupole time-of-flight (Q-TOF) mass spectrometer and a Q-Exactive Orbitrap instrument in positive ion mode, in contrast to two-step peptide fragmentation in an ion-trap mass spectrometer (reference Anal. Chem. 85, 7044-7051 (30)). In the hybrid Q-TOF and Q-Exactive inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Orbitraps were found to be comparable or even outperform QTof in the analytical characterization of small molecules in various contexts (metabolomics, drugs, etc. ), 14–20 as well as in the identification and quantification of proteins using both bottom‐up and intact methods 21–25 . Studies of peptide fragmentation in HCD cells, the appropriate choice of experimental parameters used in proteomics, and studies on the transferability of results and experimental setup between the two instruments are all of significant importance.…”
Section: Introductionmentioning
confidence: 99%
“…Orbitraps were found to be comparable or even outperform QTof in the analytical characterization of small molecules in various contexts (metabolomics, drugs, etc. ), 14–20 as well as in the identification and quantification of proteins using both bottom‐up and intact methods 21–25 . Studies of peptide fragmentation in HCD cells, the appropriate choice of experimental parameters used in proteomics, and studies on the transferability of results and experimental setup between the two instruments are all of significant importance.…”
Section: Introductionmentioning
confidence: 99%
“…including proteins, [1][2][3][4][5][6][7][8][9][10][11] glycans, [12][13][14][15][16][17][18][19][20][21] lipids, [22][23][24][25] and nucleic acids [26][27] . A free radical is generated by three major methods, collision-induced dissociation (CID) of fragile bonds, photodissociation (PD) of fragile bonds, and electron activated dissociation (ExD including ECD and ETD).…”
mentioning
confidence: 99%
“…As a CIDbased technique, free radical-initiated peptide sequencing mass spectrometry (FRIPS-MS) has made a significant advancement and has recently gained popularity in the field of proteomics. [1][2][3][4][5][6][7] FRIPS-MS relies on radical-induced dissociation initiated by the generation of hydrogen-deficient radicals, which is generated mainly via homolytic dissociation of fragile bonds by either photoactivation or collision induced dissociation (CID). 5,[7][8] In 2004, Porter's group first demonstrated that free radical-induced peptide cleavage can be initiated by collisional activation of the weak peroxide bond that was added to the peptide via sitespecific modification of the ε-amino group of lysine residues or the N-terminus.…”
mentioning
confidence: 99%
See 2 more Smart Citations